Transfer of cow's milk beta-lactoglobulin to human serum after a milk load: a pilot study. - Lovegrove, J A (1993)
A sensitive and specific enzyme linked immunosorbent assay (ELISA) was developed for the quantification of cow's milk beta-lactoglobulin in human serum. The assay had a sensitivity of 80 pg/ml (2 standard deviations from zero) and did not cross react significantly with any other tested milk proteins. The absorption of cow's milk beta-lactoglobulin and beta-lactoglobulin immunoglobulin G antibody levels after a milk load was investigated in eight healthy non-allergic individuals. There was a significant variation in the circulating beta-lactoglobulin antigen levels during the six hour period after feeding (p < 0.01) for the combined data. A biphasic absorption pattern was seen in all subjects except one subject who had undetectable levels. No significant variation with time was observed for the beta-lactoglobulin IgG antibody levels and no correlation was found between the beta-lactoglobulin antigen levels and the beta-lactoglobulin IgG antibody levels. This pilot study offered information on the quantity of immunogenic cows' milk protein transferred to the blood after a milk load in non-allergic healthy adults and confirmed a biphasic profile of antigen transfer. The sensitivity of the assay used has shown that transfer of food antigen does occur in the majority of healthy nonallergic subjects.